Developing E-Module of Islamic Reading Text Materials - Astri Winandari Berlin; Rahayu Apriliaswati; Yanti Sri Rezeki (Journal of Foreign Language Teaching and Learning, 2022)
Providing English learning material with an Islamic basis for Madrasah Aliyah students is important as the students are Islamic learners. This research aims to develop an e-module of Islamic reading text materials for the second semester of tenth-grade students of MAN 1 Pontianak. The researchers adapted the Analyze, Design, and Develop phases of the ADDIE concept to develop this research product. The analysis phase was conducted by interviewing the English teacher to determine the suitable e-module to be designed. The design phase was done by designing the contents of the e-module based on the analysis results. The e-module consists of recount and narrative texts materials with Islamic-based stories and integrates the values of aqidah (strong belief), tawakkul (reliance upon Allah), tolerance, hard work, and husnuzon (positive thinking). In the development phase, the researchers developed the e-module then checked it with a self-designed standard evaluation checklist. The result showed that the e-module already fulfilled the criteria of appropriateness. The e-module could be supplementary reading materials to make the students’ autonomous learning easier. It was written in easy-to-understand language and provided self-instructional material with independent self-evaluation. Specifically, it is expected to improve their understanding of recount and narrative text materials and strengthen their Islamic character values.